PROPHETIC PEDAGOGY–BASED DIDACTICAL DESIGN TO ENHANCE RELIGIOUS ATTITUDES IN ELEMENTARY STUDENTS - Yoyo Zakaria Ansori; Mohamad Gilar Jatisunda; Ahmad Rifqy Ash-Shiddiqy; Dendi Irawan (Universitas Majalengka, 2025)
The limited engagement of students in religious practices and the dominance of normative, dogmatic character education hinder the reflective internalization of religious values. This study explores the integration of prophetic pedagogy within a Didactical Design Research (DDR) framework to foster religious attitudes among elementary school students. Conducted over 16 weeks in a fifth-grade class at SDN Babakan Jawa I, Majalengka, the study involved 20 students and two teachers. The research identified three main learning obstacles—ontogenic, epistemological, and didactic—which were addressed through tailored didactical interventions such as structured reflection journals, role-playing, contextualized examples, scaffolded exercises, and student-centered learning. Findings show that these strategies significantly improved students’ moral reasoning, reflective thinking, empathy, and the application of religious values in real-life contexts. The study demonstrates that prophetic pedagogy, when implemented through DDR, can create transformative, contextual, and value-oriented learning experiences. This approach contributes a practical model for character education rooted in reflective religious understanding.